MODEL PENDIDIKAN KARAKTER DALAM KISAH LUQMAN AL-HAKIM - Fika Fitrotin Karomah; Ali Rahmat (Institut Kariman Wirayudha Sumenep, 2022)
The purpose of this study was to determine the model of character education in the story of Lukman al-Hakim. The approach used is a qualitative approach as a research approach and library research as a type of research. The data collection procedure used the documentation method. While the data analysis technique used descriptive data analysis. Based on the results of an in-depth study of the character education model contained in the Qashashul Qur'an verse, the results of the research indicate that the character education model in the Luqman al-hakim story consists of character education goals which include the formation of human beings, moral development, values the basic values ​​of character education (not arrogant, strong ideals, earnest in seeking knowledge, courtesy, helping, patient, forgiving, responsible, sincere, not easily discouraged, dare to admit mistakes, love God and all His creation, gratitude, no shirk, compassion, obedience to both parents, leadership and social care), as well as the stages of character education through moral education, aqidah education and shari'ah education.